CHALLENGES FOR FORMULATING NATURAL COSMETICS: COMPARATIVE PHYSICOCHEMICAL STUDIES ON NATRUAL AND SYNTHETIC MADE SHAMPOO - SAMUELRAJ ISAIAH,; SHANMUGAM KARTHIKEYAN, (International Journal of Pharma and Bio Sciences, 2015)
There has been a gradual increase in trends towards preparations of natural cosmetics due to its impressive efficacy, sustainability, non-toxicity, and feel of living with nature. Different words were being used by the cosmetic industry in label claims as Natural, Organic, Herbal, Vegetable, and Green ingredients. These magical words create a mass of confusion among the customers to choose the right product. This article deals with preparation of natural shampoo and its comparative physicochemical evaluation with synthetic made shampoo. It also discusses the challenges faced by the formulators/manufacturers to formulate a completely natural shampoo.